Accounting information systems (AIS) and their effect on strategic decision-making - Jawad, Mohammed Majeed (Technium Social Sciences Journal, 2023)
Accounting information systems have a major role in assisting the administration about making various decisions, as well as in drawing up the strategic plans of the bank. Therefore, the research focused on measuring the impact of accounting information systems on making strategic decisions for a group of banks. At the required level, or are there obstacles that led to poor use of information systems in general, The SPSS v.25 programme and the Excel programme were used on a sample of 38 branch and department managers in a sample of Iraqi banks, and the results showed that accounting information systems contributed to the strategic decision-making of the bank. The research sample and the two researchers recommend that AIS be updated in line with the expansion of the bank’s activities in providing financial services to ensure the effectiveness of the system and its role in correcting the strategic decision.